2015
DOI: 10.1103/physrevlett.114.170502
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Random Access Codes Using Singled-Level Systems

Abstract: Random access codes (RACs) are used by a party to, with limited communication, access an arbitrary subset of information held by another party. Quantum resources are known to enable RACs that break classical limitations. Here, we study quantum and classical RACs with high-level communication. We derive average performances of classical RACs and present families of high-level quantum RACs. Our results show that high-level quantum systems can significantly increase the advantage of quantum RACs over their classi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
152
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(153 citation statements)
references
References 27 publications
(36 reference statements)
1
152
0
Order By: Relevance
“…In terms of efficiency, it has been demonstrated, both theoretically and experimentally, that quantum protocols reduce the information transfer required to perform some specific distributed computational tasks . Some of these schemes provide an exponential advantage with respect to their classical counterparts while, at the same time, quantum systems also allow for a decrease in the amount of physical resources necessary for communication …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of efficiency, it has been demonstrated, both theoretically and experimentally, that quantum protocols reduce the information transfer required to perform some specific distributed computational tasks . Some of these schemes provide an exponential advantage with respect to their classical counterparts while, at the same time, quantum systems also allow for a decrease in the amount of physical resources necessary for communication …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] Some of these schemes provide an exponential advantage with respect to their classical counterparts while, at the same time, quantum systems also allow for a decrease in the amount of physical resources necessary for communication. [19][20][21][22][23][24] Along these lines, a recent theoretical result [25] has shown that, by means of quantum superposition, it is possible to perform two-way communication between two distant parties which only exchange a single particle. Such an operation is impossible in classical physics, where two-way communication can be realized only if the parties exchange two particles, one per party, or if the same particle goes back and forth between them.…”
mentioning
confidence: 99%
“…Evaluating (1) it is straightforward to find the average success probability p Q 2,d = 1/2 + 1/2 √ d. These specific QCRACs were shown to be optimal (at least) for d = 2, 3, 4, 5 [19]. In comparison, the optimal classical success probability is strictly smaller: p C 2,d = 1/2 + 1/2d [19].…”
mentioning
confidence: 99%
“…[19] and the experimental technique can be modified to realize the 2 (3) → 1 QCRAC, and (ii) EARACs have an important advantage over QCRACs in the sense that multiple copies of a basic EARAC can be used to implement a significantly more complex EARAC. Therefore, complex EARACs can be implemented without increasing the qualitative experimental complexity in terms of the requirements on state preparation and measurements for the basic 2 (3) → 1 EARAC.…”
mentioning
confidence: 99%
See 1 more Smart Citation